Electrophoretic particles, their manufacturing method and applications
By incorporating a core layer with lower density core particles and gaps, the electric swimming particles achieve enhanced stability and reduced light leakage, addressing the limitations of conventional designs for display technologies.
Patent Information
- Application Number
- JP2024525725
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-17
- Filing Date
- 2022-12-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-15
AI Technical Summary
Conventional electric swimming particles with a core shell structure face challenges in controlling the thickness of the shell layer, leading to poor stability and light leakage issues, which hinder their application in display technologies.
The particles are designed with a core layer containing multiple core particles, where the core particles have a lower density than the shell layer, and gaps between them, forming a wrinkle structure that enhances adhesion and reduces overall particle diameter, preventing light leakage and improving stability.
The design results in improved movement speed and stability of the particles, reducing light leakage and sedimentation, making them suitable for large-scale manufacturing and display applications.
Smart Images

Figure 2025502592000001_ABST
Abstract
Description
[Technical field]
[0001] This disclosure claims priority to a Chinese patent application filed with the China Patent Office on December 17, 2021, bearing application number 202111550520.6 and entitled "Electrophoretic Particles and Their Manufacturing Method and Application," the entire contents of which are incorporated herein by reference. The present disclosure relates to the technical field of electrophoretic particles, and in particular to electrophoretic particles and their manufacturing method and application. [Background technology]
[0002] Electrophoretic display has the advantages of low energy consumption, good sunlight readability, low production cost and flexible manufacturing, so it currently stands out among many display technologies and has become one of the flexible electronic display technologies with great development potential. The display mechanism of electrophoretic display technology is that charged electrophoretic particles of different colors are moved by an electric field to display the required pattern.
[0003] Electrophoretic particles having a core-shell structure can effectively reduce the density of the electrophoretic particles and can bring the density of the electrophoretic particles closer to the density of the electrophoretic liquid. As a result, the electrophoretic particles have the advantages of excellent bistability and short response time, and are preferably used.
[0004] Core-shell structure particles are generally divided into two types: inner-layer core display and outer-layer shell display. The inner-layer core display type has serious light leakage due to the existence of a transparent shell, so the general core-shell structure adopts a shell layer display type. The core-shell structure particles with shell layer display have high requirements for the properties and thickness of the shell layer material, and it is necessary to ensure that the phenomenon of light leakage does not occur, and it is also necessary to control the volume and density of the material so that the core-shell particles have a certain stability. However, in the actual manufacturing process, it is difficult to balance the properties of the core-shell particles in various aspects, so that the properties of the core-shell particles are prone to light leakage, or the density is high, resulting in defects such as poor stability, which makes them insufficient for application in the display field. Summary of the Invention [Problem to be solved by the invention]
[0005] The present disclosure provides electrophoretic particles, as well as their manufacturing methods and applications, in order to solve the problem that electrophoretic particles having a core-shell structure in the prior art cannot well control the thickness of the shell layer, resulting in poor particle stability and poor use effect. [Means for solving the problem]
[0006] To achieve the above objectives, the present disclosure employs the following technical solutions:
[0007] The electrophoretic particles according to the first embodiment include a shell layer and a core layer coated in the shell layer. The core layer includes a plurality of core particles, and the density of the core particles is lower than the density of the shell layer.
[0008] In some embodiments, there are voids between the core particles in the core layer.
[0009] In some embodiments, the voids occupy between 5% and 15% of the volume of the core layer.
[0010] In some embodiments, the core layer occupies between 30% and 80% of the volume of the electrophoretic particles.
[0011] In some embodiments, the density of the core particle is at least half the density of the shell layer.
[0012] In some embodiments, the density of the shell layer is less than 3 g / cm 3 ~5.6g / cm 3 It is.
[0013] In some embodiments, the density of the core particle is less than 1 g / cm 3 ~2.8g / cm 3 It is.
[0014] In some embodiments, the particle diameter of the electrophoretic particles is 300 to 1000 nm.
[0015] In some embodiments, the particle size of the core particle is from 10 nm to 50 nm.
[0016] In some embodiments, the material of the shell layer is more than 70% reflective to visible light or more than 80% absorptive to visible light.
[0017] In some embodiments, the material of the shell layer comprises an inorganic pigment and the core particle comprises an inorganic particle or an organic particle.
[0018] In certain embodiments, the inorganic particulate material comprises at least one of silica, alumina, and magnesium oxide.
[0019] In some embodiments, the material of the organic particles includes at least one of polymethylmethacrylate, polystyrene, and polyvinylpyrrolidone.
[0020] In some embodiments, the inorganic pigment comprises at least one of titanium dioxide, zirconium oxide, zinc oxide, copper chrome black, and iron manganese black.
[0021] A method for producing electrophoretic particles according to a second embodiment includes the steps of: Providing a precursor material for producing a shell layer and core particles; a step of dispersing core particles and an organic solvent to obtain a first core particle dispersion liquid, mixing a precursor material and an organic solvent to obtain a first precursor material mixture liquid, and dropping the first precursor material mixture liquid into the first core particle dispersion liquid to mix and heat react with each other to obtain electrophoretic particles, Or, Providing a precursor material for producing a shell layer and core particles; The method includes the steps of dispersing core particles and an organic solvent to obtain a second core particle dispersion liquid having a saturated concentration, mixing a precursor material and an organic solvent to obtain a second precursor material mixed liquid having a mass percentage concentration of 5% to 35%, and dropping the second core particle dispersion liquid into the second precursor material mixed liquid to mix, heat and react with each other to obtain electrophoretic particles.
[0022] In certain embodiments, the precursor material includes any one or more of ethyl titanate, isopropyl titanate, tetrabutyl titanate, titanium tetrachloride, zirconium propoxide, ferrous chloride, ferrous sulfate, zinc nitrate, zinc chloride, zinc sulfate, copper nitrate, and chromium nitrate.
[0023] In some embodiments, the method further comprises the step of sonicating the first core particle dispersion, and the sonication time is between 20 minutes and 2 hours.
[0024] In some embodiments, the drip rate is between 0.1 mL / s and 0.12 mL / s.
[0025] In some embodiments, the temperature of the mixed and heated reaction is 50°C to 55°C.
[0026] In some embodiments, the time for mixing, heating and reacting is 24 hours to 26 hours.
[0027] An electrophoretic display liquid according to a third aspect contains electrophoretic particles selected from the above electrophoretic particles, or electrophoretic particles manufactured by the above electrophoretic particle manufacturing method.
[0028] A display electronic paper according to a fourth aspect includes electrophoretic particles selected from the above electrophoretic particles, or electrophoretic particles manufactured by the above electrophoretic particle manufacturing method. Effect of the Invention
[0029] The electrophoretic particles according to the first embodiment of the present disclosure include a shell layer and a core layer coated in the shell layer, and the core layer includes a plurality of core particles. The plurality of core particles are configured so that a wrinkle structure is formed in the shell layer coated on the surface, and as the surface area of the core layer increases, the number of groups on the surface of the core particles that are bonded to the shell layer increases, and the adhesion between the shell layer and the core layer is improved. The shell layer of the obtained electrophoretic particles has a strong compactness, so that the overall particle size of the electrophoretic particles is appropriately reduced, the motion speed of the electrophoretic particles in the electric field is improved, and it is ensured that the electrophoretic particles do not cause a light leakage phenomenon. Furthermore, since the density of the core particles is smaller than the density of the shell layer, the density of the obtained electrophoretic particles is smaller, the settling speed of the electrophoretic particles when the electric field is removed is suppressed, and the dispersion stability of the electrophoretic particles is improved, so that the parts have good steady performance.
[0030] The method for producing electrophoretic particles according to the second aspect of the present disclosure includes two different production methods. The first production method provides a core particle dispersion and a precursor material mixture for producing a shell layer, respectively, and then adds the precursor material mixture to the core particle dispersion in a dropwise manner and heats it to promote the precursor material to deposit on the core particle surface to form a single-layer shell layer, thereby obtaining electrophoretic particles. The second production method provides a core particle dispersion having a saturated concentration and a precursor material mixture for producing a shell layer, respectively, and drips the core particle dispersion with a saturated concentration into the precursor material mixture with a relatively low concentration, so that the core particle dispersion does not diffuse rapidly, and it is ensured that the concentrated solution and the dilute solution are mixed as a homogeneous phase solution and electrophoretic particles containing a plurality of core particles are formed. Both of the two production methods are simple, convenient, and easy to operate. The production method can produce electrophoretic particles with agile movement, strong dispersion stability, and no light leakage phenomenon, which is suitable for large-scale production.
[0031] Since the electrophoretic display liquid according to the third aspect of the present disclosure contains electrophoretic particles that are quick to move, have strong dispersion stability, and do not cause light leakage, the resulting electrophoretic display liquid has excellent performance and is advantageous for a wide range of applications.
[0032] Since the display electronic paper according to the fourth aspect of the present disclosure contains electrophoretic particles that are quick to move, have strong dispersion stability, and do not cause light leakage, the resulting display electronic paper has excellent display effect and is advantageous for wide application. [Brief description of the drawings]
[0033] In order to more clearly describe the means in the embodiments of the present disclosure, the following briefly introduces the drawings required in the description of the embodiments. Obviously, the drawings in the following description are only some embodiments of the present disclosure, and those skilled in the art can also obtain other drawings based on these drawings without creative labor. [Figure 1] 1A to 1C are schematic diagrams illustrating a method for producing electrophoretic particles according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0034] In order to clarify the technical problems, technical solutions and technical effects to be solved by the present disclosure, the present disclosure will be described in more detail below with reference to examples. Note that the specific examples described herein are merely for the purpose of illustrating the present disclosure and are not intended to limit the present disclosure.
[0035] In this disclosure, the term "and / or" describes a relationship between related objects and indicates that three relationships can exist. For example, A and / or B can indicate that A exists alone, A and B exist together, or B exists alone. Here, A and B may be singular or plural. The character " / " generally indicates that the related objects before and after are in an "or" relationship.
[0036] In this disclosure, "at least one" means one or more, and "multiple" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of one or more items. For example, "at least one of a, b, or c" or "at least one of a, b, and c" can each represent a, b, c, ab, ac, bc, or abc, where a, b, and c can be one or more.
[0037] In addition, in each embodiment of the present disclosure, the size of the numbers of each process does not mean the order of execution, and some or all of the steps may be executed in parallel or one after the other. The order of execution of each process should be determined by its function and internal logic, and is not a limitation on the implementation process of the embodiment of the present disclosure.
[0038] The terms used in the embodiments of the present disclosure are merely for the purpose of describing particular embodiments and are not intended to limit the present disclosure. Furthermore, as used in the embodiments of the present disclosure and the appended claims, the singular forms "a," "an," and "the" are intended to include the plural forms unless the context clearly dictates otherwise.
[0039] The weight of the relevant components in the embodiments of the present disclosure may indicate not only the specific content of each component, but also the proportional relationship between the weights of each component. Therefore, as long as the content of the relevant components in the embodiments of the present disclosure is proportionally increased or decreased, it falls within the range described in the embodiments of the present disclosure. Specifically, the mass in the embodiments of the present disclosure may be in mass units well known in the chemical industry, such as μg, mg, g, kg, etc.
[0040] The terms "first" and "second" are merely used for descriptive purposes and are used to distinguish objects such as materials, etc., and should not be understood as indicating or implying a relative importance or number of such technical features. For example, a first XX may be referred to as a second XX, and similarly, a second XX may be referred to as a first XX, without departing from the scope of the embodiments of the present disclosure. Thus, a feature qualified with "first" or "second" may explicitly or implicitly include one or more features.
[0041] An electrophoretic particle according to a first aspect of an embodiment of the present disclosure includes a shell layer and a core layer coated within the shell layer, the core layer including a plurality of core particles, and the density of the core particles being smaller than the density of the shell layer.
[0042] The electrophoretic particles according to the first embodiment of the present disclosure include a shell layer and a core layer coated in the shell layer, and the core layer includes a plurality of core particles. The plurality of core particles are configured so that a wrinkle structure is formed in the shell layer coated on the surface, and as the surface area of the core layer increases, the number of groups on the surface of the core particles bonded to the shell layer increases, and the adhesion between the shell layer and the core layer is improved. The shell layer of the obtained electrophoretic particles has a strong compactness, so that the overall particle size of the electrophoretic particles is appropriately reduced, the motion speed of the electrophoretic particles in the electric field is improved, and the electrophoretic particles are guaranteed not to cause a light leakage phenomenon. Furthermore, since the density of the core particles is smaller than the density of the shell layer, the density of the obtained electrophoretic particles is smaller, and the settling speed of the electrophoretic particles when the electric field is removed is suppressed, and the dispersion stability of the electrophoretic particles is improved, so that the parts have good steady performance.
[0043] In some embodiments, the density of the core particles is less than the density of the shell layer, further reducing the density of the electrophoretic particles and improving the migration speed of the electrophoretic particles.
[0044] In some embodiments, the core layer has gaps between the core particles, and the gaps are filled with air, which is favorable for reducing the density of the entire core layer, so that the density of the resulting core layer is smaller than that of the core particles, the density of the electrophoretic particles is reduced, the settling velocity of the electrophoretic particles is suppressed when the electric field is removed, and the dispersion stability of the electrophoretic particles is improved, so that the part has good steady-state performance.
[0045] In some embodiments, the voids occupy 5% to 15% of the volume of the core layer. The density and stability of the core layer are controlled by controlling the volume occupancy of the voids in the core layer. The lower the volume occupancy of the voids in the core layer, the higher the density of the core layer, but the higher the stability of the resulting core layer. The higher the volume occupancy of the voids in the core layer, the lower the density of the core layer, but the stability of the formed core layer decreases accordingly, and the core layer may collapse, which is disadvantageous for forming electrophoretic particles.
[0046] In some specific embodiments, the volume fraction of voids in the core layer is selected from 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, and 15%.
[0047] In some embodiments, the core layer occupies 30% to 80% of the volume of the electrophoretic particles. Specifically, the occupancy rate of the core layer is mainly determined based on the diameter of the electrophoretic particles, and when the diameter of the electrophoretic particles is small, the occupancy rate of the core layer is low, so that the phenomenon of light leakage from the electrophoretic particles is avoided. When the diameter of the electrophoretic particles is large, the occupancy rate of the core layer increases accordingly, the density of the electrophoretic particles decreases, and the moving speed of the electrophoretic particles in electrolysis is improved.
[0048] In some specific embodiments, the volume of the electrophoretic particles occupied by the core layer is selected from 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, and 80%.
[0049] In some embodiments, the density of the core particles is less than or equal to half the density of the shell layer. Tight control of the density of the core particles can ensure that the density of the resulting electrophoretic particles is small, suppress the settling velocity of the electrophoretic particles when the electric field is removed, and improve the dispersion stability of the electrophoretic particles, thereby providing the part with good steady-state performance.
[0050] In some embodiments, the density of the shell layer is less than 3 g / cm 3 ~5.6g / cm 3 The shell layer is mainly used for display. When the display requirements are different, those skilled in the art can select appropriate color-producing materials, but for the same color display, the lower the density of the material, the lower the density of the electrophoretic particles produced.
[0051] In some embodiments, the density of the core particle is 1 g / cm 3 ~2.8g / cm 3Decreasing the density of the core particles is favorable for decreasing the density of the electrophoretic particles, improving the dispersion stability of the electrophoretic particles, and making the parts have good steady performance. In addition, those skilled in the art can understand that the matching and bonding stability between the core particles and the shell layer should be considered when selecting the core particles.
[0052] In some embodiments, the particle diameter of the electrophoretic particles is 300nm to 1000nm. This allows the electrophoretic particles to move quickly in an electric field, and ensures that the properties of the manufactured parts are excellent. If the particle diameter of the electrophoretic particles is too large, the movement speed of the electrophoretic particles in an electric field is too slow, which tends to deteriorate the display effect of the parts, and is disadvantageous in use. In some specific embodiments, the particle diameter of the electrophoretic particles is selected from 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, and 1000nm.
[0053] In some embodiments, the particle diameter of the core particles is 10-50 nm, and when the particle diameter of the electrophoretic particles is constant, the content of the core particles can be controlled by controlling the particle diameter of the core particles, which is advantageous for controlling the dispersion stability of the electrophoretic particles and improving the denseness of the shell layer. If the particle diameter of the core particles is too small, the core particles tend to aggregate, which is disadvantageous for the formation of the core layer. If the particle diameter of the core particles is too large, it is difficult to form a good structure of the multi-core particles, which affects the properties of the electrophoretic particles.
[0054] In some specific embodiments, the particle size of the core particle is 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm.
[0055] In some embodiments, the material of the shell layer of the electrophoretic particles has a reflectance of greater than 70% to visible light or an absorptance of greater than 80% to visible light.
[0056] In some embodiments, the material of the shell layer includes a material having high light reflectance and low light transmittance when used to manufacture electrophoretic particles that utilize the reflective properties of the particles to display, such as white display. In some embodiments, the shell layer material for manufacturing white electrophoretic particles has a visible light reflectance of more than 70%. By selecting a material having a visible light reflectance of more than 70% as the shell layer material, more than 70% of the external light can be reflected, which is advantageous for improving the display effect of the white electrophoretic particles.
[0057] In some embodiments, the material of the shell layer includes a material with high light absorption rate when the particles are used to manufacture electrophoretic particles that display by utilizing their light absorbing properties, such as black display, etc. In some embodiments, the shell layer material for manufacturing black electrophoretic particles has an absorptivity of more than 80% for visible light, and a material with an absorptivity of more than 80% for visible light is selected as the shell layer material, which can absorb more than 80% of external light, and is advantageous for improving the display effect of the black electrophoretic particles.
[0058] In some embodiments, the material of the shell layer comprises an inorganic pigment. Since the obtained electrophoretic particles are of a shell layer display type, in the core-shell structure particles of the shell layer display, the material of the shell layer is usually a material having high light reflectance and low light transmittance or a material having high light absorptance.
[0059] In some embodiments, the inorganic pigment comprises at least one of titanium dioxide, zirconium oxide, zinc oxide, copper chrome black, and iron manganese black. The shell layer of the electrophoretic particles produced by the inorganic pigment employed can reflect or absorb a large amount of light, since the inorganic pigment itself has high reflectivity or absorptivity to light, and it is ensured that the electrophoretic particles obtained are less likely to have a light leakage phenomenon.
[0060] In some embodiments, the core particles include inorganic particles or organic particles. In some embodiments, the material of the inorganic particles includes at least one of silica, alumina, and magnesium oxide. In some embodiments, the material of the organic particles includes at least one of polymethylmethacrylate, polystyrene, and polyvinylpyrrolidone.
[0061] In some specific embodiments, the electrophoretic particles include Fe 3 O 4 Shell material: SiO 2 Electrophoretic particles formed by coating the core particles, TiO 2 Shell material: SiO 2 Electrophoretic particles formed by coating the core particles, TiO 2 The present invention includes, but is not limited to, any one of electrophoretic particles formed by coating PMMA core particles with shell material. Those skilled in the art can further determine the material of the core particles according to the shell layer material, ensure that there is strong binding stability between the core particles and the shell layer material, and obtain electrophoretic particles with excellent properties.
[0062] A method for producing electrophoretic particles according to a second embodiment of the present disclosure includes the steps of: Providing a precursor material for producing a shell layer and core particles; a step of dispersing core particles and an organic solvent to obtain a first core particle dispersion liquid, mixing a precursor material and an organic solvent to obtain a first precursor material mixture liquid, and dropping the first precursor material mixture liquid into the first core particle dispersion liquid to mix and heat react with each other to obtain electrophoretic particles, Or, Providing a precursor material for producing a shell layer and core particles; The method includes the steps of dispersing core particles and an organic solvent to obtain a second core particle dispersion liquid having a saturated concentration, mixing a precursor material and an organic solvent to obtain a second precursor material mixed liquid having a mass percentage concentration of 5% to 35%, and dropping the second core particle dispersion liquid into the second precursor material mixed liquid to mix, heat and react with each other to obtain electrophoretic particles.
[0063] The method for producing electrophoretic particles according to the second embodiment of the present disclosure includes two different production methods. When the two different production methods are used for production, both are simple, convenient, and easy to operate. The production method can produce electrophoretic particles with quick movement, strong dispersion stability, and no light leakage phenomenon, and is suitable for large-scale production.
[0064] In some embodiments, a method for producing electrophoretic particles includes: S01: Providing a precursor material for producing a shell layer and a core particle; S02 includes a step of dispersing core particles and an organic solvent to obtain a first core particle dispersion, mixing a precursor material and the organic solvent to obtain a first precursor material mixed solution, and dropping the first precursor material mixed solution into the first core particle dispersion to mix, heat and react with each other to obtain electrophoretic particles.
[0065] In this manufacturing method, a core particle dispersion liquid and a precursor material mixture liquid for producing a shell layer are separately obtained, and then the precursor material mixture liquid is added dropwise to the core particle dispersion liquid and heated to promote deposition of the precursor material on the core particle surface to form a single shell layer, thereby obtaining electrophoretic particles.
[0066] Step S01 provides precursor materials and core particles for producing a shell layer.
[0067] In some embodiments, the material of the core particle includes any one or more of silica, alumina, magnesium oxide, polymethylmethacrylate, polystyrene, and polyvinylpyrrolidone.
[0068] In certain embodiments, the precursor material includes any one or more of ethyl titanate, isopropyl titanate, tetrabutyl titanate, titanium tetrachloride, zirconium propoxide, ferrous chloride, ferrous sulfate, zinc nitrate, zinc chloride, zinc sulfate, copper nitrate, and chromium nitrate.
[0069] In some specific embodiments, the precursor material is ethyl titanate, which can form hydroxyl groups on the surface of titanium atoms through hydrolysis with organic solvents and weak alkaline solutions, and when mixed with the core particle solution, it is easy to adsorb with the hydroxyl groups on the surface of the core particles and deposit on the surface of the core particles to obtain a single-layer shell material.
[0070] In step S02, the core particles and the organic solvent are dispersed to obtain a first core particle dispersion. By dispersing the core particles in the organic solvent to obtain a dispersion of the core particles, hydroxyl groups are formed on the surfaces of the core particles, which is advantageous for bonding with the shell layer material. Furthermore, ultrasonic treatment is performed to control the electrophoretic particles formed thereafter to have a structure including a plurality of core particles.
[0071] In some embodiments, organic solvents include, but are not limited to, methanol, ethanol.
[0072] In some embodiments, the method further includes a step of ultrasonically treating the first core particle dispersion, and the ultrasonic treatment time is 20 minutes to 2 hours. By controlling the length of the ultrasonic treatment time, the number of core particles contained in the obtained electrophoretic particles can be controlled.
[0073] Furthermore, the precursor material and the organic solvent are mixed to obtain a first precursor material mixture.
[0074] In some embodiments, a hydrolysis aid can be added depending on the precursor material to facilitate the subsequent synthesis steps. In some specific embodiments, when the precursor material is ethyl titanate, a weak alkaline solution can be added during the reaction to promote the hydrolysis of ethyl titanate in the solution.
[0075] Furthermore, the first precursor material mixture is dropped into the first core particle dispersion, and mixed and heated to cause a reaction, thereby obtaining electrophoretic particles.
[0076] In some embodiments, the dripping speed is 0.1 mL / s to 0.12 mL / s. With an appropriate dripping speed, the precursor material is deposited on the surface of the core particles after hydrolysis, forming electrophoretic particles having a single shell layer and multiple core particles.
[0077] In some embodiments, the temperature of the heating reaction treatment is 50°C to 55°C. The temperature control of the heating reaction treatment is advantageous to control the formation of the shell layer. If the heating temperature is too high, the reaction rate is too fast and the shell layer is not dense enough. If the heating reaction temperature is too low, the reaction efficiency is too low, which is disadvantageous for industrial production.
[0078] In some embodiments, the time of the heat reaction treatment is 24 hours to 26 hours. Controlling the treatment time of the heat reaction is advantageous to form a complete shell layer structure. If the reaction time is too short, defects may occur in the formed shell layer, if the reaction time is too long, the formed shell layer is too thick, which is disadvantageous to the density reduction of the electrophoretic particles, and if the reaction time is too long, the reaction efficiency is too low, which is disadvantageous to industrialized production.
[0079] In some other embodiments, a method for producing electrophoretic particles includes: G01 providing a precursor material for producing a shell layer and a core particle; G02 includes a step of dispersing core particles and an organic solvent to obtain a second core particle dispersion liquid having a saturated concentration, mixing a precursor material and an organic solvent to obtain a second precursor material mixed liquid having a mass percentage concentration of 5% to 35%, and dropping the second core particle dispersion liquid into the second precursor material mixed liquid to mix, heat and react with each other to obtain electrophoretic particles.
[0080] The manufacturing method provides a core particle dispersion liquid having a saturated concentration and a precursor material mixed liquid for manufacturing a shell layer, and the saturated core particle dispersion liquid is dropped into a precursor material mixed liquid having a relatively low concentration. Since the core particle dispersion liquid does not diffuse rapidly, the concentrated solution and the dilute solution are mixed into a homogeneous phase solution, and electrophoretic particles containing a plurality of core particles are formed.
[0081] In step G01, a precursor material for producing a shell layer and core particles are provided, where the selection of the core particles and shell layer material precursor is the same as that in step S01, and the description is omitted here.
[0082] In step G02, the core particles and the organic solvent are dispersed to obtain a second core particle dispersion liquid having a saturated concentration, the precursor material and the organic solvent are mixed to obtain a second precursor material mixed liquid having a mass percentage concentration of 5% to 35%, and the second core particle dispersion liquid is dropped into the second precursor material mixed liquid to be mixed, heated and reacted to obtain electrophoretic particles.
[0083] In some embodiments, organic solvents include, but are not limited to, methanol, ethanol.
[0084] In some embodiments, the precursor material and the organic solvent are mixed to obtain a second precursor material mixture, where the mass percentage of the second precursor material mixture is 5%-35%. By controlling the mass percentage of the second precursor material mixture to be low, it is ensured that the concentrated solution and the dilute solution are mixed into a homogeneous solution and electrophoretic particles including a plurality of core particles are formed.
[0085] In some embodiments, the second core particle dispersion is dropped into the second precursor material mixture and mixed and heated to react to obtain electrophoretic particles. In this reaction step, the saturated core particle dispersion is dropped into the second precursor material mixture with a relatively low concentration, and the core particle dispersion does not diffuse rapidly, so that the concentrated solution and the dilute solution are mixed as a homogeneous solution, and electrophoretic particles containing a plurality of core particles are formed.
[0086] In some embodiments, the dropping speed is 0.1 mL / s to 0.12 mL / s. At an appropriate dropping speed, the saturated core particle dispersion is dropped into the relatively low concentration shell layer material precursor solution, and the core particle dispersion does not diffuse rapidly, so that the concentrated solution and the dilute solution are mixed as a homogeneous phase solution, and electrophoretic particles containing a plurality of core particles are formed.
[0087] In some embodiments, the temperature of the heating reaction treatment is 50°C to 55°C. The temperature control of the heating reaction treatment is advantageous to control the formation of the shell layer. If the heating temperature is too high, the reaction rate is too fast and the shell layer is not dense enough. If the heating reaction temperature is too low, the reaction efficiency is too low, which is disadvantageous for industrial production.
[0088] In some embodiments, the heating reaction time is 24 to 26 hours, and the heating reaction time is controlled to be favorable for forming a complete shell layer structure. If the reaction time is too short, defects may occur in the formed shell layer, and if the reaction time is too long, the reaction efficiency is too low, which is unfavorable for industrial production.
[0089] In some embodiments, the resulting electrophoretic particles are further grafted with organic matter for subsequent use in charging.
[0090] In some specific embodiments, KH570 is grafted onto the surface of electrophoretic particles. The method for producing the same specifically includes: D01: Providing and mixing γ-methacryloxypropyltrimethoxysilane (KH570) and an organic solvent to obtain a KH570 solution, and dispersing electrophoretic particles in the organic solvent to obtain an electrophoretic particle dispersion; D02: Dropping the KH570 solution into the electrophoretic particle dispersion, reacting at 50 to 55° C. for 1 to 2 hours, and then filtering, washing and drying to obtain KH570-grafted electrophoretic particles.
[0091] In some embodiments, organic solvents include, but are not limited to, methanol, ethanol.
[0092] In some specific embodiments, PDMC is grafted onto the surface of the electrophoretic particles, and the method for producing the same specifically comprises: R01: A step of mixing KH570 graft electrophoretic particles and an organic solvent to obtain a KH570 graft electrophoretic particle dispersion; R02 A step of mixing azobisisobutyronitrile (AIBN), methacryloyloxyethyltrimethylammonium chloride (DMC), and an organic solvent to obtain a charged mixed solution; R03 Dropping the charged mixed solution into the KH570 graft electrophoretic particle dispersion, reacting at 80°C for 8 to 8.5 hours, and then filtering, washing and drying to obtain electrophoretic particles of polymethacryloyloxyethyltrimethylammonium chloride (PDMC) with positively charged surfaces.
[0093] An electrophoretic display liquid according to a third aspect of the embodiment of the present disclosure includes electrophoretic particles selected from the above electrophoretic particles, or electrophoretic particles manufactured by the above electrophoretic particle manufacturing method.
[0094] Since the electrophoretic display liquid according to the third aspect of the present disclosure contains electrophoretic particles that are quick to move, have strong dispersion stability, and do not cause light leakage, the resulting electrophoretic display liquid has excellent performance and is advantageous for a wide range of applications.
[0095] A display electronic paper according to a fourth aspect of the embodiment of the present disclosure includes electrophoretic particles selected from the above electrophoretic particles, or electrophoretic particles manufactured by the above electrophoretic particle manufacturing method.
[0096] Since the display electronic paper according to the fourth aspect of the present disclosure contains electrophoretic particles that are quick to move, have strong dispersion stability, and do not cause light leakage, the resulting display electronic paper has excellent display effect and is advantageous for wide application.
[0097] The present invention will be described below with reference to specific examples.
[0098] [Example 1] <Electrophoretic particles and their manufacturing method> <Electrophoretic particles> The electrophoretic particles include a shell layer and a core layer coated in the shell layer, the core layer includes a plurality of core particles, and there are voids between the plurality of core particles, the core particles are silica, the shell layer is titanium dioxide, the particle diameter of the core particles is 10 nm, the particle diameter of the electrophoretic particles is 300 nm, the core layer occupies 30% of the volume of the electrophoretic particles, and the voids occupy 5% of the volume of the core layer.
[0099] <Method of Manufacturing Electrophoretic Particles> Based on the electrophoretic particles according to Example 1, core particles and shell layer material precursors were provided.
[0100] 8 g of silica nanoparticles and 50 g of absolute ethanol were thoroughly dispersed and stirred, and then subjected to ultrasonic treatment for 20 minutes to obtain a first core particle dispersion.
[0101] Ethyl titanate, absolute ethanol, and 50% ammonia water were mixed to obtain a first shell material precursor mixture.
[0102] The first shell material precursor mixture was added dropwise to the first core particle dispersion and mixed and heated to obtain multi-core core-shell structured electrophoretic particles, where the dropwise addition rate was 0.1 mL / s, the temperature of the mixed and heated reaction was 50° C., and the time of the mixed and heated reaction was 24 hours.
[0103] [Example 2] <Electrophoretic particles and their manufacturing method> <Electrophoretic particles> The electrophoretic particles include a shell layer and a core layer coated in the shell layer, the core layer includes a plurality of core particles, and there are voids between the plurality of core particles, the core particles are silica, the shell layer is titanium dioxide, the particle diameter of the core particles is 20 nm, the particle diameter of the electrophoretic particles is 400 nm, the core layer occupies 35% of the volume of the electrophoretic particles, and the voids occupy 6% of the volume of the core layer.
[0104] <Method of Manufacturing Electrophoretic Particles> Based on the electrophoretic particles according to the second embodiment, a core particle and a shell layer material precursor are provided.
[0105] 8 g of silica nanoparticles and 50 g of absolute ethanol were thoroughly dispersed and stirred to obtain a core particle dispersion liquid with a saturated concentration.
[0106] Ethyl titanate, absolute ethanol, and 50% aqueous ammonia were mixed to obtain a shell layer material precursor mixture with a mass percent concentration of 30%.
[0107] The core particle dispersion liquid was dropped into the shell layer material precursor mixture and mixed and heated to produce electrophoretic particles with a multi-core-shell structure, where the drop rate was 0.1 mL / s, the temperature of the mixed and heated reaction was 50° C., and the time of the mixed and heated reaction was 24 hours.
[0108] [Example 3] <Electrophoretic particles and their manufacturing method> <Electrophoretic particles> The electrophoretic particles include a shell layer and a core layer coated in the shell layer, the core layer includes a plurality of core particles, and there are voids between the plurality of core particles, the core particles are alumina, the shell layer is titanium dioxide, the particle diameter of the core particles is 30 nm, the particle diameter of the electrophoretic particles is 500 nm, the core layer occupies 40% of the volume of the electrophoretic particles, and the voids occupy 10% of the volume of the core layer.
[0109] <Method of Manufacturing Electrophoretic Particles> The preparation method was the same as in Example 1, except that 50% aqueous ammonia was replaced with urea, to obtain the corresponding core-shell nanoparticles.
[0110] [Example 4] <Electrophoretic particles and their manufacturing method> <Electrophoretic particles> The electrophoretic particles include a shell layer and a core layer coated in the shell layer, the core layer includes a plurality of core particles, and there are voids between the plurality of core particles, the core particles are magnesium oxide, the shell layer is titanium dioxide, the particle diameter of the core particles is 35 nm, the particle diameter of the electrophoretic particles is 500 nm, the core layer occupies 50% of the volume of the electrophoretic particles, and the voids occupy 12% of the volume of the core layer.
[0111] <Method of Manufacturing Electrophoretic Particles> The preparation method was the same as in Example 1, except that 50% aqueous ammonia was replaced with hexamethylenetetramine, to obtain the corresponding core-shell nanoparticles.
[0112] [Example 5] <Electrophoretic particles and their manufacturing method> <Electrophoretic particles> The electrophoretic particles include a shell layer and a core layer coated in the shell layer, the core layer includes a plurality of core particles, and there are voids between the plurality of core particles. The core particles are polymethylmethacrylate, the shell layer is titanium dioxide, the particle diameter of the core particles is 40 nm, the particle diameter of the electrophoretic particles is 700 nm, the core layer occupies 70% of the volume of the electrophoretic particles, and the voids occupy 13% of the volume of the core layer.
[0113] <Method of Manufacturing Electrophoretic Particles> The preparation method was the same as in Example 1, except that 50% ammonia water was replaced with hexamethylenetetramine, and the room temperature ethanol solution was replaced with 0°C ethanol solution, and the corresponding core-shell structured nanoparticles were obtained.
[0114] [Example 6] <Electrophoretic particles and their manufacturing method> <Electrophoretic particles> The electrophoretic particles include a shell layer and a core layer coated in the shell layer, the core layer includes a plurality of core particles, and there are voids between the plurality of core particles, the core particles are silica, the shell layer is titanium dioxide, the particle diameter of the core particles is 45 nm, the particle diameter of the electrophoretic particles is 800 nm, the core layer occupies 70% of the volume of the electrophoretic particles, and the voids occupy 5% of the volume of the core layer.
[0115] <Method of Manufacturing Electrophoretic Particles> Corresponding core-shell nanoparticles were obtained in the same manner as in Example 2, except that 50% ammonia water was replaced with hexamethylenetetramine and the dropping speed of the ethanol solution was changed from 0.1 mL / s to 0.12 mL / s.
[0116] [Example 7] <Electrophoretic particles and their manufacturing method> <Electrophoretic particles> The electrophoretic particles include a shell layer and a core layer coated in the shell layer, the core layer includes a plurality of core particles, and there are voids between the plurality of core particles, the core particles are silica, the shell layer is titanium dioxide, the particle diameter of the core particles is 50 nm, the particle diameter of the electrophoretic particles is 1000 nm, the core layer occupies 80% of the volume of the electrophoretic particles, and the voids occupy 15% of the volume of the core layer.
[0117] <Method of Manufacturing Electrophoretic Particles> The same procedure as in Example 2 was followed, except that 50% ammonia water was replaced with hexamethylenetetramine, and the reaction time after the dropwise addition was changed to 26 hours, to obtain the corresponding core-shell nanoparticles.
[0118] [Comparative Example 1] <Electrophoretic particles and their manufacturing method> <Electrophoretic particles> The electrophoretic particles are nanoparticles with a single-core type core-shell structure, the core particle is silica, the shell layer is titanium dioxide, the particle diameter of the core particle is 5 nm, the particle diameter of the electrophoretic particles is 500 nm, and the core layer occupies 90% of the volume of the electrophoretic particles.
[0119] <Method of Manufacturing Electrophoretic Particles> The preparation method was the same as in Example 1 to obtain the corresponding core-shell structured nanoparticles.
[0120] [Comparative Example 2] <Electrophoretic particles and their manufacturing method> <Electrophoretic particles> The electrophoretic particles are nanoparticles having a single-core type core-shell structure, the core particle being made of silica, the shell layer being made of titanium dioxide, the particle diameter of the core particle being 100 nm, and the thickness of the shell layer being 200 nm.
[0121] <Method of Manufacturing Electrophoretic Particles> The preparation method was the same as in Example 2 to obtain the corresponding single-core type core-shell structured nanoparticles.
[0122] The electrophoretic particles according to Examples 1 to 7 and Comparative Examples 1 and 2 are subjected to a charged graft treatment. The charged graft treatment is carried out by the following method: a step of mixing γ-methacryloxypropyltrimethoxysilane (KH570) with an organic solvent to obtain a KH570 solution, dispersing the electrophoretic particles obtained in Examples 1 to 7 and Comparative Examples 1 to 2 in the organic solvent to obtain an electrophoretic particle dispersion, dropping the KH570 solution into the electrophoretic particle dispersion and reacting at 50 to 55° C. for 1 to 2 hours, and further filtering, washing, and drying to obtain KH570-grafted electrophoretic particles including the electrophoretic particles according to Examples 1 to 7 and Comparative Examples 1 to 2; and mixing the KH570 grafted electrophoretic particles with an organic solvent to obtain a KH570 grafted electrophoretic particle dispersion liquid, mixing azobisisobutyronitrile (AIBN), methacryloyloxyethyltrimethylammonium (DMC) and an organic solvent to obtain a charged mixed solution, dropping the charged mixed solution into the KH570 grafted electrophoretic particle dispersion liquid and reacting at 80°C for 8 to 8.5 hours, and then filtering, washing and drying to obtain electrophoretic particles of polymethacryloyloxyethyltrimethylammonium chloride (PDMC) having positively charged surfaces, including the electrophoretic particles according to Examples 1 to 7 and Comparative Examples 1 and 2.
[0123] <Performance test> For the electrophoretic particles of polymethacryloyloxyethyl trimethylammonium chloride (PDMC) whose surface is positively charged, including the electrophoretic particles according to Examples 1-7 and Comparative Examples 1-2, the white L value of the electronic paper film piece was measured in the all-white display mode and the normal operation mode, and the white L value of the comparative example was defined as 70. In the all-white display mode, five points are selected and averaged on the screen, and points are selected at the four corners and the center, respectively. In the operation mode, five points are similarly selected and averaged on the screen, and points are selected at the four corners and the center, respectively. Since the operation mode is a black and white display effect, it is necessary to avoid the black area when selecting points, and obtain the data of the all-white display mode and the operation mode, respectively, and provide a calculation basis based on such data.
[0124] <Result analysis> For electrophoretic particles of polymethacryloyloxyethyltrimethylammonium chloride (PDMC) with positively charged surfaces, including the electrophoretic particles according to Examples 1 to 7 and Comparative Examples 1 and 2, the L value of the electronic paper was measured in both the all-white display mode and the normal operation mode, and the results are shown in Table 1. In Table 1, the white effect of the comparative example is defined as 70, and the results in Table 1 show that the electrophoretic particles obtained in Examples 1 to 7 have a better white display effect than the comparative example products in both the all-white display mode and the normal operation mode.
[0125] Therefore, the electrophoretic particles according to the embodiment of the present disclosure are particles having a multi-core structure, and the number of groups on the surface of the core that are bonded to the shell layer is increased, so that the bond adhesion between the shell layer and the core is improved, and the shell layer of the obtained electrophoretic particles has a strong compactness, so that the thickness of the shell layer can be appropriately reduced, and the overall volume of the electrophoretic particles can be reduced, which is favorable for the electrophoretic particles to move rapidly under the electric field, and the white display mode effect can be improved. In addition, the density of the electrophoretic particles having the multi-core core-shell structure formed is smaller, which not only improves the response speed of the electrophoretic particles, but also reduces the settling speed of the particles when the electric field is removed, and improves the dispersion stability of the particles, so that the parts have good steady performance.
[0126] [Table 1]
[0127] The above description is merely the preferred embodiment of the present disclosure, and is not intended to limit the present disclosure. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present disclosure should be included within the protection scope of the present disclosure.
Claims
1. A shell layer; A core layer coated within the shell layer; Including, The core layer includes a plurality of core particles, and the density of the core particles is lower than the density of the shell layer.
2. The electrophoretic particle according to claim 1 , wherein in the core layer, there are gaps between the multiple core particles.
3. 3. The electrophoretic particle according to claim 2, wherein the voids occupy 5% to 15% of the volume of the core layer.
4. 2. The electrophoretic particle according to claim 1, wherein the core layer occupies 30% to 80% of the volume of the electrophoretic particle.
5. The electrophoretic particle according to claim 1 , wherein the density of the core particle is equal to or less than half the density of the shell layer.
6. The density of the shell layer is 3 g / cm 3 ~5.6g / cm 3 and The density of the core particles is 1 g / cm 3 ~2.8g / cm 3 6. The electrophoretic particle according to claim 5, wherein
7. The particle diameter of the electrophoretic particles is 300 nm to 1000 nm, 7. The electrophoretic particle according to claim 1, wherein the core particle has a particle diameter of 10 nm to 50 nm.
8. 7. The electrophoretic particle according to claim 1, wherein the material of the shell layer has a reflectance to visible light of more than 70% or an absorptance to visible light of more than 80%.
9. the material of the shell layer includes an inorganic pigment; The electrophoretic particle according to claim 1 , wherein the core particle comprises an inorganic particle or an organic particle.
10. the inorganic particle material comprises silica; the material of the organic particles includes at least one of polymethyl methacrylate, polystyrene, and polyvinylpyrrolidone; 10. The electrophoretic particles of claim 9, wherein the inorganic pigment comprises at least one of titanium dioxide, zirconium oxide, zinc oxide, copper chrome black, and iron manganese black.
11. A method for producing electrophoretic particles according to any one of claims 1 to 10, comprising the steps of: Providing a precursor material for producing a shell layer and core particles; a step of dispersing the core particles and an organic solvent to obtain a first core particle dispersion liquid, mixing the precursor material and the organic solvent to obtain a first precursor material mixture liquid, dropping the first precursor material mixture liquid into the first core particle dispersion liquid, and mixing and heating the mixture to cause a reaction, thereby obtaining electrophoretic particles; Including, Or, Providing a precursor material for producing a shell layer and core particles; a step of dispersing the core particles and an organic solvent to obtain a second core particle dispersion liquid having a saturated concentration, mixing the precursor material and the organic solvent to obtain a second precursor material mixed liquid having a mass percent concentration of 5% to 35%, dropping the second core particle dispersion liquid into the second precursor material mixed liquid, mixing and heating to cause a reaction, and obtaining electrophoretic particles; A method for producing electrophoretic particles, comprising:
12. the precursor material comprises any one or more of ethyl titanate, isopropyl titanate, tetrabutyl titanate, titanium tetrachloride, zirconium propoxide, ferrous chloride, ferrous sulfate, zinc nitrate, zinc chloride, zinc sulfate, copper nitrate, and chromium nitrate; The method for producing electrophoretic particles according to claim 11 .
13. The method further includes a step of ultrasonically treating the first core particle dispersion, the ultrasonic treatment time being 20 minutes to 2 hours; The dripping rate is 0.1 mL / s to 0.12 mL / s.
12. The method for producing electrophoretic particles according to claim 11, wherein the temperature of the mixing and heating reaction is 50° C. to 55° C., and the time of the mixing and heating reaction is 24 hours to 26 hours.
14. An electrophoretic display liquid comprising electrophoretic particles selected from the electrophoretic particles according to any one of claims 1 to 10, or electrophoretic particles produced by the method for producing electrophoretic particles according to any one of claims 11 to 13.
15. 14. An electronic paper for display comprising electrophoretic particles selected from the electrophoretic particles according to any one of claims 1 to 10, or electrophoretic particles produced by the method for producing electrophoretic particles according to any one of claims 11 to 13.
Citation Information
Patent Citations
Nucleocapsid particles for electrolyte display device
CN1438531A
Method for producing mini-suspension emulsions or suspensions of submicron shell / core particles
JP2010509060A
Electrophoretic particle and optical path control member comprising same
WO2021054686A1